Method for producing capacitor element having dielectric ceramic film, paste for producing dielectric ceramic film, and capacitor element having dielectric ceramic film

By optimizing the stoichiometric ratio of ceramic powder and organic media, a (1-x)[0.8(0.94Na0.5Bi0.5TiO3·0.06BaTiO3)·x BiAlO3 dielectric ceramic film was prepared, and the materials in the high temperature range in the prior art were solved. The problems of internal stability and dielectric loss achieve stable performance and low loss within -83°C to 550°C, and are suitable for high-temperature capacitors.

CN119317983APending Publication Date: 2025-01-14TECH UNIV DARMSTADT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380044445.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-14
Filing Date
2023-06-13
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

In the prior art, materials based on Na0.5Bi0.5TiO3 or BaTiO3 cannot achieve stable capacity and low dielectric loss within an industrial important temperature range of -50°C to ≥300°C, making it difficult to meet the needs of high-temperature capacitor components.

Method used

Using a specific stoichiometric ratio of ceramic powder with oxides Bi2O3, TiO2, ZrO2 and Al2O3, and carbonate Na2CO3, BaCO3 to organic media, by adding 1-butanol, tributyl acetyl citrate, dispersant and binding , a dielectric ceramic film of (1-x) [0.8 (0.94Na0.5Bi0.5TiO3·0.06BaTiO3)·x BiAlO3 was prepared, and the slurry manufacturing process was optimized to improve temperature stability and capacitance performance.

Benefits of technology

The stable relative dielectric constant and low dielectric loss of dielectric ceramic films in -83°C to 550°C are achieved, and are suitable for capacitor applications under high temperature and high voltage conditions, with a maximum operating temperature range of -68°C to 391°C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119317983A_ABST
    Figure CN119317983A_ABST
Patent Text Reader

Abstract

The invention relates to a method (1) for producing a capacitor element having a dielectric ceramic film (9), to a paste for producing a dielectric ceramic film (9), and to a capacitor element having a dielectric ceramic film (9). In the slurry manufacturing step, a slurry is manufactured from a ceramic powder and an organic medium. At least the oxides Bi2O3, TiO2, ZrO2 and Al2O3 and at least the carbonates Na2CO3, BaCO3 and CaCO3 or the respective precursors of the oxides and / or carbonates are used in stoichiometric ratios in a ceramic powder to synthesize (1-x) [0.8 (0.94 Na0. 5Bi0. 5TiO3. 0.06 BaTiO3). 0.2 CaZrO3]. X BiAlO3, where x = 0.5, 1, 1.5, 2, 4 and 8 mol%. In a film casting step, the slurry is cast into a film, in which an electrode (10) is applied to the cast film in an electrode application step, and in which the cast film equipped with the electrode (10) is sintered at an elevated temperature in a sintering step. The organic medium has at least one liquid solvent containing at least 1-butanol, at least one plasticizer containing acetyl tributyl citrate, at least one dispersant and at least one binder.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a method for producing a capacitor element having a dielectric ceramic film, wherein in a slurry production step, a slurry is produced from ceramic powder and an organic medium, wherein at least oxides Bi2O3, TiO2, ZrO2 and Al2O3 and at least carbonates Na2CO3, BaCO3 and CaCO3 or respective precursors of said oxides and / or carbonates are used in a stoichiometric ratio for the ceramic powder to synthesize (1-x)[0.8(0.94Na 0.5 Bi 0.5 TiO3·0.06BaTiO3)·0.2CaZrO3]·x BiAlO3, wherein x=0.5, 1, 1.5, 2, 4 and 8 mol %, and wherein the slurry is cast into a thin film in a film casting step, and wherein an electrode is applied to the cast film in an electrode applying step, and wherein the cast film provided with the electrode is sintered at an elevated temperature in a sintering step to remove the organic medium from the structure and convert the cast film into a dielectric ceramic film, wherein the dielectric ceramic film comprises at least (1-x)[0.8(0.94Na 0.5 Bi 0.5 TiO3·0.06BaTiO3)·0.2CaZrO3]·xBiAlO3, where x=0.5, 1, 1.5, 2, 4 and 8 mol%.

[0002] The present invention also relates to a slurry for producing a dielectric ceramic film, wherein the slurry has a ceramic powder and an organic medium, wherein the ceramic powder has at least oxides Bi2O3, TiO2, ZrO2 and Al2O3 and at least carbonates Na2CO3, BaCO3 and CaCO3 or respective precursors of the oxides and / or carbonates.

[0003] The present invention also relates to a capacitor element having a dielectric ceramic film having at least (1-x)[0.8(0.94Na 0.5 Bi 0.5 TiO3·0.06BaTiO3)·0.2CaZrO3]·xBiAlO3, wherein x=0.5, 1, 1.5, 2, 4 and 8 mol %, wherein the dielectric ceramic film has an electrode, and wherein the ceramic film is made of a slurry, wherein the slurry has a ceramic powder and an organic medium.

[0004] Capacitors are passive electronic components that are installed in almost all electronic applications. Capacitors are used in aerospace, the automotive industry or in portable consumer electronics. A capacitor can consist of at least one capacitor element as well as other connections and lines required for contacting the capacitor element. A capacitor element has a dielectric in the form of a dielectric film and electrodes arranged on the dielectric film. Films are considered to be various thin layers that are suitable in terms of size for shielding the electrodes of the capacitor element as a dielectric component so that with the help of this capacitor element, electric charges and the associated energy can be stored statically in the electric field of the capacitor. As part of an electrical circuit, a capacitor element should have properties that are as stable as possible over a large temperature range and at high applied voltages, wherein at the same time the capacitor element is required to be smaller and smaller in size and have constant or improved properties. In addition, high demands are placed on the reliability and life of these passive electronic components.

[0005] Capacitor elements with aluminum or aluminum oxide films or polymer films are usually used as dielectric films. Due to the structure and properties of these dielectric films, such passive components can only be used within a certain upper temperature limit, which usually does not exceed 120°C. Above this temperature limit, dielectric ceramic films are usually used. Capacitor elements of this type have one or more dielectric ceramic films as dielectrics instead of temperature-sensitive polymer films or aluminum films.

[0006] In order to push the upper temperature limit to temperatures far above 120° C., various systems are known in the prior art. In order to meet the requirements of high-temperature capacitor components, for example, based on Na 0.5 Bi 0.5 TiO3(NBT) or BaTiO3(BT) systems or their solid solutions are considered as promising materials (Ren, P., He, J., Sun, L., T., Wan, Y., Yang, S., Zhao, G. (2019), Journal of the European Ceramic Society, 39(14), 4160–4167). However, due to the complex defect chemistry of NBT-based materials and their solutions, it has been impossible to find materials with stable capacity and low dielectric loss tanδ of less than 2% in the industrially important temperature range of -50°C to ≥300°C (Zeb, A., & Milne, SJ (2015), Journal of Materials Science: Materials in Electronics, 26(12), 9243–9255). Recently, a material system that can meet the temperature range set by industry has been known. Among them, the material system is (1-x)[0.8(0.94Na 0.5 Bi 0.5TiO3·0.06BaTiO3)·0.2CaZrO3]·x BiAlO3. This material system has the oxides sodium bismuth titanate, barium titanate, calcium zirconate and bismuth aluminate (Hoang, A. P., Steiner, S., Yang, F., Li, L., Sinclair, D. C., & T. (2021), Journal of the European Ceramic Society, 41(4), 2587–2595).

[0007] Capacitor elements are usually made from slurries. Slurries are understood to mean mixtures of ceramic powders and organic media. For this purpose, the ceramic powders can have air-resistant reactants, such as oxides and / or carbonates and mixtures thereof, which, when weighed in a suitable stoichiometric ratio to one another, can be sintered in a solid-state reaction to form the desired dielectric ceramic film.

[0008] The organic medium enables optimal mixing of the individual components of the ceramic powder before sintering. After its production, the slurry can be cast as a film in a film casting step.

[0009] The properties of the sintered paste depend largely on the composition of the paste, the process steps carried out to make the paste and the parameters used during the process and thus largely determine the final properties of the capacitor element.

[0010] The object of the present invention is to improve the methods known from the prior art for producing capacitor elements with dielectric ceramic films, slurries for producing dielectric ceramic films, and capacitor elements with dielectric ceramic films.

[0011] According to the invention, this object is achieved by a method for producing a capacitor element with a dielectric ceramic film, wherein the organic medium has at least one liquid solvent containing at least 1-butanol, at least one plasticizer containing acetyl tributyl citrate, at least one dispersant and at least one binder.

[0012] According to the invention, capacitor elements with dielectric ceramic films can be produced from the slurry according to the invention, which have particularly advantageous properties. The material system optimized by this synthesis is particularly suitable for use at elevated temperatures or increased temperature fluctuations and high voltages during operation. In addition, it provides high energy storage density and high efficiency and at the same time low dielectric losses in the temperature range considered.

[0013] The properties of the dielectric ceramic film obtained are derived in particular from the method for producing the slurry. The oxides Bi2O3, TiO2, ZrO2 and Al2O3 and the carbonates Na2CO3, BaCO3 and CaCO3 are preferably weighed in such a stoichiometric ratio to one another that the slurry in the sintering step can be sintered to (1-x)[0.8(0.94Na 0.5 Bi 0.5 TiO3·0.06BaTiO3)·0.2CaZrO3]·xBiAlO3. The best properties described here are obtained in the range of x=0.5, 1, 1.5, 2, 4 and 8 mol %. However, it is particularly preferred that the ceramic powder is weighed so that after sintering, 0.995[0.8(0.94Na 0.5 Bi 0.5 TiO3·0.06BaTiO3)·0.2CaZrO3]·0.005BiAlO3. The dielectric ceramic film made of this slurry shows a stable relative dielectric constant in the range of -83°C to 550°C, with fluctuations of only ≤15% and a maximum value of 630 at 1kHz. The dielectric loss tanδ≤0.02 is stable in the range of -68°C to 391°C, so the maximum use range for use as a capacitor element is -68°C to 391°C.

[0014] As mentioned above, the composition and ratio of materials used in the slurry are crucial for the performance of the dielectric ceramic film thus made. In the slurry manufacturing step, an organic medium is added in addition to the ceramic powder. The organic medium comprises at least one liquid solvent containing at least 1-butanol. Compared with solvents known in the prior art such as ethanol and / or 2-butanone, the advantage provided by using 1-butanol is that, compared with the aforementioned solvents, 1-butanol evaporates more slowly, so that the ceramic powder has enough time to settle and form the densest or most dense filling of each particle of the ceramic powder after mixing with the organic medium. However, in addition to 1-butanol, other solvents can also be used, particularly in the temperature range of synthesis (i.e. at room temperature) in liquid form and at room temperature with a solvent having an evaporation rate similar to 1-butanol. Due to the rapid evaporation of ethanol or 2-butanone, cavities may be generated due to the thus limited sedimentation, and on the other hand, due to uneven filling and therefore uneven distribution, secondary phases may be increased after the sintering step. Such secondary phases can significantly impair the properties of the final dielectric ceramic film, since the resulting secondary phases cannot be removed or can be removed only with increased effort.

[0015] Acetyl tributyl citrate is advantageously used as a plasticizer. The task of the plasticizer is to keep the casting film flexible after casting. It is known from the prior art that polyethylene glycol is used as a plasticizer, for example. Unlike hygroscopic polyethylene glycol, acetyl tributyl citrate is not hygroscopic. During the slurry manufacturing process, or even during the storage time, when using hygroscopic plasticizers, water may accumulate on the plasticizer itself (even if it is only on the surface) or penetrate into the depths of the slurry structure. The water molecules accumulated on the surface or present in the structure can evaporate in the sintering step of the slurry, so that when they leave the structure, pores are left, which locally interfere with the structure here on the one hand, but on the other hand may also change and reduce the final density and therefore the desired performance of the element. On the contrary, acetyl tributyl citrate does not accumulate a large amount of water, so that the final density of the element is not significantly affected by the use of this plasticizer. In addition to using acetyl tributyl citrate, other plasticizers that do not have hygroscopic properties can also be used. Furthermore, the use of acetyl tributyl citrate may represent a more biohazardous and therefore more environmentally friendly decision compared to, for example, the widely used phthalates.

[0016] Dispersants are understood to mean generally molecular compounds which are able to prevent agglomeration for a certain period of time by accumulating on dissolved particles, in the present case particles of ceramic powder. This is achieved in that direct accumulation can be prevented by bonding dispersant molecules to first particles, i.e. further second particles directly contact the first particles, so that the all-round accumulation of the dispersant spatially prevents agglomeration of the individual particles. A large number of dispersants are known from the prior art, among which are, for example, oleic acid and / or its derivatives. However, oleic acid and / or its derivatives have only a very low oxidation resistance under normal conditions. The decomposition products resulting from the decomposition of these non-oxidation-resistant oleic acids and / or derivatives can significantly limit the final density of the cast film, which can lead to changes in the properties of the final dielectric ceramic film. For this reason, it is preferred to use dispersants which are characterized by a very high stability and which do not attack the cast film during storage and / or do not themselves decompose due to external influences. Thus, the dispersant advantageously has a structure which effectively assists the separation of the individual particles in the slurry or mud, for example by a particularly spatially desirable arrangement of the chains and / or side chains. Furthermore, as already mentioned, the dispersants used should be thermodynamically and chemically resistant. Furthermore, the dispersants are preferably bound as firmly as possible to the individual ceramic particles so that they cannot be squeezed off their surface quickly. Experiments have shown that it is particularly advantageous to use the dispersants from the manufacturer Lubrizol. M387.

[0017] The binder determines by its structure the arrangement of the ceramic particles during the production of the slurry in the slurry production step, wherein the components of the slurry are arranged relative to one another by means of the binder. In this process, the binder burns off during the sintering process, i.e. is oxidized into volatile gas components and is thus removed from the structure. The binder determines by its three-dimensional structure the arrangement of the individual particles and thus the position of one another. After the sintering process, only a dielectric ceramic film made of ceramic powder remains, the structure of which is largely determined by the binder. Preferably, a binder can be used which, due to its size and its properties, binds to the surface of the particles and thus also acts as a dispersant. PVB from the manufacturer Kuraray Europe GmbH LP BX860 in particular has proven to be advantageous as an adhesive.

[0018] The organic medium formed by a liquid solvent containing at least 1-butanol, at least one plasticizer containing at least acetyl tributyl citrate, at least one dispersant and at least one binder can be mixed with the ceramic powder in the slurry production step until a sufficiently uniform mixture is achieved. The ceramic powder itself can be made of the mentioned oxides and carbonates. On the one hand, the oxides and / or carbonates can be mixed into a mixture beforehand and then combined with the organic medium, or the oxides and carbonates can be combined and mixed with the organic medium at the same time.

[0019] Furthermore, it is optionally conceivable that, instead of using carbonates and / or oxides directly, precursors of oxides and / or carbonates are used which react in the sintering step to form (1-x)[0.8(0.94Na 0.5 Bi 0.5 TiO3 · 0.06BaTiO3) · 0.2CaZrO3] · xBiAlO3, for example, with the oxide according to the invention as an intermediate step. In addition, carbonates and / or oxides can be made from precursors before being added to the organic medium in the slurry manufacturing step. For example, ZrO2 can be obtained from ZrSiO4 at high temperature.

[0020] In order to achieve the desired composition, the oxides and / or carbonates and / or their precursors used should preferably be used in the highest possible purity, including in particular a purity of ≥99.975% for Bi2O3, a purity of ≥99.6% for TiO2, a purity of ≥99.5% for ZrO2, a purity of ≥99.95% for Al2O3, a purity of ≥99.5% for Na2CO3, a purity of ≥99.8% for BaCO3, and a purity of ≥99.5% for CaCO3.

[0021] Optionally, provision is made that, in order to produce the slurry in the slurry production step, 55 to 65% by weight of ceramic powder, 24 to 37% by weight of solvent, 0.28 to 0.38% by weight of dispersant, 3.0 to 5.5% by weight of plasticizer and 4.5 to 5.5% by weight of binder are used, wherein the weight percentages add up to 100% by weight. In order to achieve the advantages of the dielectric ceramic film mentioned at the outset, it is particularly advantageous to use the aforementioned ratios of the individual components of the slurry.

[0022] In an alternative embodiment of the concept of the invention, it is provided that at least polyvinyl butyral is used as a binder. The binder ensures that the individual particles of the ceramic powder are arranged in a particularly advantageous manner relative to one another. The polyvinyl butyral can also have different contents of polyvinyl alcohol and polyvinyl acetate. However, a polyvinyl alcohol content of 18 to 21% by weight and a polyvinyl acetate content of 8 to 14% by weight are particularly advantageously provided.

[0023] In an alternative embodiment, it is provided that in the slurry manufacturing step, oxide and / or carbonate are heat-treated to obtain anhydrous oxide and / or carbonate. In order to obtain the required film composition in the synthesis of dielectric ceramic film, it is particularly advantageous to weigh the reactant used in a stoichiometric ratio as accurately as possible. By using the oxide and / or carbonate used in anhydrous and therefore precisely defined state, stoichiometric weighing is made easy. Anhydrous state is understood to refer to a state that does not contain a significant amount of crystal water (hydrate) in the crystal structure, or does not have an oxide and / or carbonate on the particles of oxide and / or carbonate with a significant amount of water molecules accumulated. In this way, it is possible to achieve as far as possible defect-free and stoichiometric weighing of oxide and / or carbonate for synthesis. Therefore, particularly when oxide and / or carbonate are stored for a long time in atmospheric air, oxide and / or carbonate can absorb or combine an uncertain amount of water, which can make weighing according to the present invention difficult due to mass changes.

[0024] One possible way to obtain anhydrous oxides and / or carbonates in a heat treatment is to expose the powders of the oxides and / or carbonates to elevated temperatures for a longer period of time in order to remove adhering water and water of crystallization from the structure. To prepare anhydrous oxides, the oxides TiO2, ZrO2, Al2O3 can be heated to a temperature of 800°C, for example for a suitable time of 8 hours, and Bi2O3 to a temperature of 300°C. The carbonate Na2CO3 can be treated at a temperature of 300°C (200°C for BaCO3 and CaCO3) for 20 hours to achieve the conversion to anhydrous form. Furthermore, it is not important in all manufactures of anhydrous oxides and / or carbonates whether the temperature is increased in a temperature ramp before the desired final temperature is reached, or whether the oxides and / or carbonates are directly subjected to the desired temperature treatment in a preheated furnace.

[0025] Preferably, the now anhydrous carbonates and / or oxides are used directly in the synthesis after drying, or they are stored in an anhydrous atmosphere before being used in the synthesis. If the oxides and / or carbonates are not used directly in the synthesis, but are precursors thereof, they can also be converted into anhydrous form in the thermal treatment. Alternatively, anhydrous modifications of the oxides and / or carbonates can also be prepared by converting suitable precursors into oxides and / or carbonates in a thermal treatment, thereby obtaining them in anhydrous form.

[0026] In addition, the ceramic powder and the organic medium can be ground into a slurry in the slurry manufacturing step. For this purpose, the ceramic powder and the organic medium can be ground into a slurry in a ball mill. The ceramic powder and the organic medium can be mixed before being added to the ball mill, or mixed in the ball mill. By grinding the components in a ball mill, a particularly fine grinding can be achieved, thereby achieving a small particle size of the ceramic powder and an optimal and uniform mixing, which produces a high-purity final product.

[0027] In an alternative embodiment of the invention, it is provided that the slurry is poured onto a biaxially oriented polyester film in the film casting step. A biaxially oriented polyester film is understood to mean a polyester film made primarily of polyethylene terephthalate, which is stretched in a longitudinal direction and in a transverse direction extending transversely to the longitudinal direction. A polyester film designed in this way makes the polyester film particularly tear-resistant, smooth and flexible by the stretching process, so that the slurry can be easily poured onto the polyester film. For this purpose, the slurry can be applied to the polyester film in the desired thickness using a suitable method (e.g. a "doctor blade process"). After the film has been cast, the film can be removed from the polyester film and further processed. Experiments have shown that, in particular Films which are biaxially oriented polyester films are particularly advantageous for this purpose.

[0028] It is further provided that the slurry is subjected to a heat treatment in a drying step after the film casting step in order to remove volatile organic medium from the structure before carrying out the sintering step. The heat treatment before the actual sintering step, in which the slurry is sintered to form a dielectric ceramic film, offers the advantage that volatile components of the organic medium as well as other volatile components, such as residual amounts of water, can be removed from the structure and therefore from the slurry. It should be noted that no actual sintering of the slurry takes place in this heat treatment step. Volatile components of the organic medium are the mentioned residual amounts of water, which are present in the ceramic powder and / or in the solvents, plasticizers, dispersants or binders used.

[0029] Particularly advantageously, the volatile components of the slurry are slowly and evenly removed from the structure during the heat treatment. To this end, the cast film can be exposed to room temperature or slightly elevated temperatures, which advantageously increase in a gradient from room temperature to the desired final temperature for the heat treatment, so that the volatile components do not suddenly expand or form gases, which in turn could damage the cast film. The removal of volatile components can also be carried out at the beginning of the sintering process. To this end, the temperature profile can be kept at a plateau during the sintering process, or the removal of volatile organic components can be carried out directly during the optionally prolonged heating process.

[0030] Furthermore, it is provided that in the electrode application step, the electrodes are printed onto the casting film. The printing of the electrodes enables the electrodes to be easily mounted onto the casting film and / or the dielectric ceramic film. The printing can be done by machine or manually.

[0031] It is further provided that in the stacking step, a plurality of cast films, each provided with electrodes, are stacked on top of one another to form a multilayer capacitor element as a component before the sintering step is carried out. A multilayer capacitor element is understood to mean an element consisting of a plurality of dielectric ceramic films provided with electrodes, which are stacked on top of one another in one direction, so that an alternating sequence of electrodes and dielectric ceramic films is produced.

[0032] Before the actual sintering step, the stack of cast films equipped with electrodes can itself be subjected to pressure and pre-pressing. For example, this can be done for a few seconds at a pressure in the single digit kN before the films are cold isostatically pressed, optionally at elevated pressure. In this way, an optimal bonding of the individual films to one another and between the electrodes and the cast film can be achieved.

[0033] In an alternative embodiment of the method according to the invention, it is provided that pressure is applied to the stacked films during the sintering step in order to counteract the expansion of the cast film. In addition to the volatile components of the organic medium in the drying step, the remaining residual components of the organic medium can be burned out of the structure in the sintering step. The burning out can take place directly during the sintering step or before the actual sintering step in a burning out step at an elevated temperature, but wherein the temperature does not yet allow the cast film to sinter. Additional ceramic powder can be mixed in during the sintering step in order to counteract excessive degassing of volatile components at high temperatures.

[0034] In order to counteract the sudden expansion of the cast film, it is advantageous to gradually increase the temperature from room temperature to the desired final temperature in order to counteract the sudden evaporation of organic components or residual water from the structure. It may also be advantageous to apply pressure to the film during the sintering step in order to maintain the original shape of the film on the one hand and to counteract expansion on the other hand.

[0035] Optionally, provision is made that a sintering step is carried out before a stacking step, wherein in the stacking step a plurality of dielectric ceramic films provided with electrodes are stacked on top of one another to form a multilayer capacitor element as a component. In addition to the already mentioned procedure of first stacking cast films, each provided with electrodes, and then carrying out a sintering process, wherein the cast films are sintered to form dielectric ceramic films, it is also provided according to the invention that firstly, in a sintering step that is carried out, the individual cast films provided with electrodes are sintered to form dielectric ceramic films, and then these are stacked to form a multilayer capacitor element.

[0036] The objects set out at the outset are also achieved by a slurry for producing a dielectric ceramic film, wherein the organic medium comprises at least one solvent containing at least 1-butanol, at least one plasticizer containing at least acetyl tributyl citrate, at least one dispersant, and at least one binder. The organic medium composed in this way, when combined with a ceramic powder, produces a slurry which is particularly suitable for synthesizing a dielectric ceramic film having at least (1-x)[0.8(0.94Na 0.5 Bi 0.5 TiO3·0.06BaTiO3)·0.2CaZrO3]·xBiAlO3, where x=0.5, 1, 1.5, 2, 4 and 8 mol %. Such a slurry can be used particularly advantageously for producing a capacitor element with a dielectric ceramic film according to any one of claims 1 to 10.

[0037] Optionally, it is provided that the slurry contains 55 to 65% by weight of ceramic powder, 24 to 37% by weight of solvent, 0.28 to 0.38% by weight of dispersant, 3 to 5.5% by weight of plasticizer and 4.5 to 5.5% by weight of binder, wherein the weight percentages add up to 100% by weight. In order to achieve the advantages mentioned above of the dielectric ceramic film, it is particularly advantageous to use a slurry produced from the ratio according to the invention of the components of the slurry.

[0038] According to an alternative embodiment, it is provided that the at least one binder comprises polyvinyl butyral. Polyvinyl butyral can act as a binder on the one hand and as a dispersant on the other hand.

[0039] The object specified at the outset is also achieved by a capacitor element having a dielectric ceramic film, wherein a paste is produced according to any one of claims 1 to 10. The paste according to the invention enables a capacitor element having particularly advantageous properties.

[0040] Optionally, it is provided that the capacitor element has a plurality of dielectric ceramic films, each provided with electrodes, as components to form a multilayer capacitor element.

[0041] Further advantageous embodiments of a method for producing a capacitor element with a dielectric ceramic film, a slurry for producing a dielectric ceramic film, and a capacitor element with a dielectric ceramic film are illustrated using the following figures. In which:

[0042] Figure 1 A schematic diagram showing a method according to the invention for producing a capacitor element having a dielectric ceramic film,

[0043] Figure 2 Shows Figure 1 Schematic diagram of a modification of the method of having a drying step and a stacking step,

[0044] Figure 3 Shows Figure 2 Schematic diagram of a modification of the method, in which the sintering step is performed before the stacking step,

[0045] Figure 4 Schematic diagram showing the temperature distribution during the sintering step,

[0046] Figure 5 A schematic diagram showing the temperature profile with a drying step and a sintering step,

[0047] Figure 6 shows a schematic diagram of the temperature distribution, wherein a drying step is performed during the sintering step,

[0048] Figure 7 A schematic diagram showing alternating films of a multilayer capacitor element,

[0049] Figure 8 shows an exemplary composition of each part in the slurry according to the present invention,

[0050] Fig. 9 The microstructure of the multilayer capacitor element consisting of a dielectric ceramic film and applied electrodes is shown by SEM images.

[0051] Fig.10 shows a temperature-dependent curve of the loss factor tan δ of the dielectric ceramic film according to the present invention relative to the prior art,

[0052] Fig.11 shows a curve of polarization according to electric field of a dielectric ceramic film according to the present invention relative to the prior art,

[0053] Fig.12 shows a curve of efficiency of the dielectric ceramic film according to the present invention as a function of the electric field, and

[0054] Fig.13 The resistance of the dielectric ceramic thin film composition according to the present invention to electric field and temperature is shown.

[0055] Figures 1 to 3 Different embodiments of a method 1 according to the invention for producing a capacitor element having a dielectric ceramic film are shown.

[0056] exist Figure 1 Detailed Description of the Invention A method 1 for producing a capacitor element having a dielectric ceramic film is shown schematically with the individual method steps.

[0057] In the initial slurry making step 2, a slurry is made from oxides Bi2O3, TiO2, ZrO2 and Al2O3, carbonates Na2CO3, BaCO3 and CaCO3 and an organic medium. The organic medium contains 1-butanol as a liquid solvent, acetyl tributyl citrate as a plasticizer, a dispersant and a binder. In the slurry making step, the ceramic powder and the organic medium are mixed with each other and ground in a ball mill until a uniform slurry is formed.

[0058] In the film casting step 3 following the slurry production step 2, the slurry is applied to a biaxially oriented polyester film in a film thickness of preferably 250 μm.

[0059] Subsequently, in the electrode application step 4, the cast film is provided with electrodes made of a silver-palladium electrode material with a metal content of 55% and a silver-palladium ratio of 70:30. To dry the printed electrodes, the cast film and the electrodes are dried in a drying oven at 75° C. for 20 minutes and at 90° C. by complete evaporation of the solvent and volatile components of the electrode material. After drying, the cast film with the electrodes can be removed from the film.

[0060] The film equipped with electrodes is subjected to pressure in a sintering step 5 and is first heated from room temperature to a temperature of 600° C. within 20 hours to burn out all organic components, wherein the temperature is further increased from 600° C. to 1100° C. at a heating rate of 5° C. / min and maintained at this temperature for two hours, and then cooled to room temperature at a cooling rate of 5° C. / min. In this sintering step 5, the slurry is sintered into (1-x)[0.8(0.94Na 0.5 Bi 0.5 TiO3·0.06BaTiO3)·0.2CaZrO3]·xBiAlO3, where x=0.5, 1, 1.5, 2, 4 and 8 mol%.

[0061] In a subsequent step, the capacitor element can then be provided with external electrodes and further contacts in order to form a capacitor from the capacitor element.

[0062] Figure 2 The Figure 1A modified method 1 for producing a capacitor element having a dielectric ceramic film, wherein the method is extended by adding the method steps of a drying step 6 and a stacking step 7.

[0063] In a drying step 6 following the film casting step 2, the cast film is subjected to a heat treatment in order to remove the volatile organic medium from the structure before proceeding to the sintering step 5. This makes it possible to remove the volatile components of the organic medium from the structure and therefore from the slurry, as well as other volatile components, such as residual amounts of water, which, in the event of sudden evaporation, could cause the slurry film to crack during the sintering step 5.

[0064] To produce a multilayer capacitor element, a plurality of cast films provided with electrodes are stacked on top of one another to form a stack in a stacking step. A multilayer capacitor element is understood to mean an element consisting of a plurality of ceramic films provided with electrodes, which are stacked on top of one another in one direction, so that an alternating sequence of electrodes and dielectric ceramic films is produced. The stacking step 7 is carried out after the electrode application step 4 and before the sintering step 5.

[0065] The stack formed by alternately casting the film and the electrode is pressed and pre-pressed by 6 kN. The stack is then cold isostatically pressed at 153 MPa in an oil bath and laminated to achieve the best possible bonding of the individual films to each other and to the electrodes. The stack pressed in this way is placed between two alumina foam plates placed in a ceramic crucible. Additional sacrificial powder made of ceramic powder prevents excessive degassing of the volatile components of the ceramic at high temperatures. The sintering step 5 is then carried out as described above.

[0066] Figure 3 Shown according to Figure 2 The method 1 of the present invention, wherein the sintering step 5 is performed before the stacking step 7.

[0067] Figures 4 to 6 The temperature programs according to the invention in the process of producing dielectric ceramic films are shown in each case in different embodiments. The temperature programs each show a curve of the temperature distribution as a function of time. The diagrams shown should only be used to represent the temperature distribution and are not shown to scale.

[0068] Figure 4 The temperature program during sintering step 5 is shown in FIG. The cast film and the applied electrode or stack are first heated from room temperature to a temperature of 600° C. within 20 hours to burn out all organic components, wherein the temperature is further increased from 600° C. to 1100° C. at a heating rate of 5° C. / min and held at this temperature for two hours, and then cooled to room temperature at a cooling rate of 5° C. / min.

[0069] Figure 5 Shows Figure 2The temperature profile of the method 1 shown, which consists of a drying step 6 and a subsequent sintering step 5, is shown in FIG. Figure 6 In the embodiment, the drying step 6 is a part of the sintering step 5.

[0070] Figure 7 Schematic representation of a multilayer capacitor element 8 is shown in . The multilayer capacitor element 8 has an alternating sequence of dielectric ceramic films 9 and electrodes 10 therebetween.

[0071] Figure 8 An exemplary composition of each part in the slurry according to the present invention is shown. The slurry contains 60.75% by weight of ceramic powder, 30.38% by weight of 1-butanol, 0.36% by weight of Solsperse M387 as a dispersant, 3.16% by weight of acetyl tributyl citrate as a plasticizer, and 5.35% by weight of PVB Mowital LPBX860 as a binder. The dielectric ceramic film 9 with such a composition surprisingly exhibits the best performance and is therefore suitable for use particularly at high temperatures, strong temperature fluctuations, and high applied electric fields. The dielectric ceramic film exhibits a stable relative dielectric constant within -83°C to 550°C, with fluctuations of ≤15% and a maximum value of 630 at 1kHz. The dielectric loss tanδ of ≤0.02 in the high temperature range is stable at -68°C to 391°C. It is therefore concluded that the maximum use temperature of the material as a capacitor element or a multilayer capacitor element is -68°C to 391°C.

[0072] Fig. 9 The microstructure of the multilayer capacitor element 8 made of the dielectric ceramic film 9 and the applied electrode 10 in the prior art 11 and the composition of the dielectric ceramic film 12 according to the present invention is shown by the SEM image. In particular, compared with the prior art 11, a more uniform structure and improved density are particularly shown, which produces the above-mentioned advantages.

[0073] Fig.10 The composition of the dielectric ceramic film 12 according to the present invention is shown in Figure 1 and the reference material 13 (Hoang, AP, Steiner, S., Yang, F., Li, L., Sinclair, DC, & T. (2021), Journal of the European Ceramic Society, 41 (4), 2587–2595) and temperature tolerance compared with the current prior art 11. The dielectric constant and loss factor tan δ are plotted as a function of temperature. Compared with the prior art 11, the composition of the dielectric ceramic film according to the present invention leads to lower dielectric losses, especially in the high temperature range, so the dielectric properties are almost the same in the selected temperature range.

[0074] Fig.11 and 12 The advantageous properties of capacitor elements based on the paste composition according to the present invention are further shown. Fig.11 shows the polarization of the ceramic dielectric film 12 according to the applied electric field, and Fig.12 The efficiency of the polarization operation is plotted as a function of the electric field. Compared to competing technologies, 2.66 J / cm 3 The extremely high energy storage density (at 32 kV / mm) and an efficiency of always >86% are achieved. The capacitor element and the multilayer capacitor element 8 are therefore suitable for use as an overvoltage protection or intermediate circuit capacitor and thus for intercepting voltage peaks or for keeping the voltage constant. In particular, the applied electric field of 32 kV / mm impressively demonstrates the reliability in the high voltage range.

[0075] Fig.13 The resistance of the composition of the dielectric ceramic film 12 according to the invention to electric field and temperature is shown. The capacity for electric field and various temperatures from 25° C. to 125° C. is plotted. The maximum change of about 13% at a field of 20 kV / mm and a temperature of 125° C. at the same time impressively shows the stability of the composition of the dielectric ceramic film 12 according to the invention to these two factors.

[0076] Reference numerals list

[0077] 1. Method for manufacturing capacitor element

[0078] 2 Slurry manufacturing steps

[0079] 2 Film casting steps

[0080] 4 Electrode application steps

[0081] 5 Sintering steps

[0082] 6 Drying Steps

[0083] 7 Stacking steps

[0084] 8 Multilayer capacitor elements

[0085] 9 Dielectric ceramic films

[0086] 10 Electrodes

[0087] 11 Prior Art

[0088] 12 Composition of dielectric ceramic film according to the present invention

[0089] 13References

Claims

1. A method (1) for producing a capacitor element having a dielectric ceramic film (9), wherein in a slurry production step (2), a slurry is produced from a ceramic powder and an organic medium, wherein at least oxides Bi2O3, TiO2, ZrO2 and Al2O3 and at least carbonates Na2CO3, BaCO3 and CaCO3 or respective precursors of said oxides and / or carbonates are used in a stoichiometric ratio for the ceramic powder to synthesize (1-x)[0.8(0.94Na 0.5 Bi 0.5 TiO3·0.06BaTiO3)·0.2CaZrO3]·xBiAlO3, wherein x=0.5, 1, 1.5, 2, 4 and 8 mol %, and wherein the slurry is cast into a thin film in a film casting step (3), and wherein an electrode (10) is applied to the cast film in an electrode applying step (4), and wherein the cast film provided with the electrode (10) is sintered at an elevated temperature in a sintering step (5) to remove the organic medium from the structure and convert the cast film into a dielectric ceramic film (9), wherein the dielectric ceramic film (9) comprises at least (1-x)[0.8(0.94Na 0.5 Bi 0.5 TiO3·0.06BaTiO3)·0.2CaZrO3]·xBiAlO3, where x=0.5, 1, 1.5, 2, 4 and 8 mol%, characterized in that The organic medium has at least one liquid solvent containing at least 1-butanol, at least one plasticizer containing acetyl tributyl citrate, at least one dispersant and at least one binder.

2. The method (1) according to claim 1, characterized in that: To produce the slurry in the slurry production step (2), 55 to 65 wt % of ceramic powder, 24 to 37 wt % of solvent, 0.28 to 0.38 wt % of dispersant, 3.0 to 5.5 wt % of plasticizer and 4.5 to 5.5 wt % of binder are used, wherein the weight % totals 100 wt %.

3. The method (1) according to claim 1 or 2, characterized in that: At least polyvinyl butyral is used as a binder.

4. The method (1) according to any one of claims 1 to 3, characterized in that In the slurry preparation step (2), the oxide and / or carbonate is heat-treated to obtain anhydrous oxide and / or carbonate.

5. The method (1) according to any one of the preceding claims, characterized in that In the slurry making step (2), ceramic powder and organic medium are ground into a slurry.

6. The method (1) according to any one of the preceding claims, characterized in that In the film casting step (3) the slurry is cast onto a biaxially oriented polyester film.

7. The method (1) according to any one of the preceding claims, characterized in that The slurry is heat treated in a drying step (6) after the film casting step (3) to remove the volatile organic medium from the structure, and then subjected to a sintering step (5).

8. Method (1) according to any one of the preceding claims, characterized in that In the electrode application step (4), the electrode (10) is printed onto the casting film.

9. The method (1) according to any one of the preceding claims, characterized in that In the stacking step (7), a plurality of cast films each provided with electrodes (10) are stacked on one another to form a multilayer capacitor element (8) as a component, and then subjected to the sintering step (5).

10. The method (1) according to claim 9, characterized in that Pressure is applied to the stacked film during said sintering step (5) to counteract the expansion of the cast film.

11. The method (1) according to any one of the preceding claims, characterized in that The sintering step (5) is performed before the stacking step (7) in which a plurality of dielectric ceramic films (9) provided with electrodes (10) are stacked on one another to form a multilayer capacitor element (8) as a component.

12. A slurry for producing a dielectric ceramic film (9), wherein the slurry comprises a ceramic powder and an organic medium, wherein the ceramic powder comprises at least the oxides Bi2O3, TiO2, ZrO2 and Al2O3 and at least the carbonates Na2CO3, BaCO3 and CaCO3 or respective precursors of said oxides and / or carbonates, characterized in that The organic medium comprises at least one solvent comprising at least 1-butanol, at least one plasticizer comprising at least acetyl tributyl citrate, at least one dispersant, and at least one binder.

13. The slurry according to claim 12, characterized in that The slurry contains 55 to 65 wt % of ceramic powder, 24 to 37 wt % of solvent, 0.28 to 0.38 wt % of dispersant, 3.0 to 5.5 wt % of plasticizer and 4.5 to 5.5 wt % of binder, wherein the wt % total 100 wt %.

14. The slurry according to claim 12 or 13, characterized in that The at least one binder comprises polyvinyl butyral.

15. A capacitor element having a dielectric ceramic film (9) having at least (1-x)[0.8(0.94Na 0.5 Bi 0.5 TiO3·0.06BaTiO3)·0.2CaZrO3]·xBiAlO3, wherein x=0.5, 1, 1.5, 2, 4 and 8 mol%, wherein the dielectric ceramic film (9) has an electrode (10), and wherein the ceramic film (9) is made of a slurry, wherein the slurry has a ceramic powder and an organic medium, characterized in that The slurry is prepared according to any one of claims 1 to 10.

16. The capacitor element according to claim 15, characterized in that The capacitor element has as a component a plurality of dielectric ceramic films (9) provided with electrodes (10) to form a multilayer capacitor element.